Anti-money laundering and its effectiveness / Huang Ching Choo ... [et al.] - Huang, Ching Choo; Amirrudin, Mira Susanti; Ahmad Noruddin, Nur Adura; Othman, Rohana (Accounting Research Institute & Faculty of Accountancy, 2014)
Anti-money laundering (AML) broadly encompasses procedures, processes, laws, or regulations designed to curtail the practice of generating funds through illicit or criminal activities. Since 2001, Malaysian law enforcement agencies have stepped up their capacities and efforts to curb money laundering. However, implementation costs incurred on AML activities could be burdensome to the regulating, enforcement, and reporting agencies. Although these efforts are generally benefi cial, assessing their effectiveness before increasing the level of AML regulation is necessary. This paper reviews literature on various approaches used to estimate money laundering and assess the effectiveness of AML. Although different measures and models are used to estimate money laundering, no model to quantify money laundering is globally acceptable. The absence of an accurate measurement of costs incurred and the difficulty in linking benefits to AML efforts pose challenges in assessing the effectiveness of AML policy. Nevertheless, the use of both crime data and perceived data on cost and effectiveness serves as a step forward in the determination of the effectiveness of AML in Malaysia.